2001
DOI: 10.1046/j.1365-2427.2001.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological deformities occurring in Belarusian chironomids (Diptera: Chironomidae) subsequent to the Chernobyl nuclear disaster

Abstract: 1. Chironomid larvae and adults were collected from several freshwater habitats around the Chernobyl site from 1990 to 1994 (4–8 years after a nuclear accident) and examined for morphological deformities. 2. Deformities were found in larvae of nine of the 13 species collected, and were most obvious in headcapsule structures, particularly the antennae, mentum, mandibles and epipharyngeal pectens. 3. In species of Chironomus, the most abundant genus, there was a positive linear relationship between the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Renewed interest on the radioresistance of midges could be witnessed after the Chernobyl nuclear reactor explosion in April 1986. Studies on the natural population of Chironomus obtained from the areas of Chernobyl fallout (Samoilenko et al 1994, Pankov and Andreev 1999, Williams et al 2001) confirmed the radio-adaptation of the local species of Chironomid midge. Various population genetics and cytogenetic analysis revealed that specific chromosomal inversions were stabilised in the irradiated natural population of C. belatonicus from the Chernobyl region (Michailova and Petrova 1994).…”
Section: Introductionmentioning
confidence: 90%
“…Renewed interest on the radioresistance of midges could be witnessed after the Chernobyl nuclear reactor explosion in April 1986. Studies on the natural population of Chironomus obtained from the areas of Chernobyl fallout (Samoilenko et al 1994, Pankov and Andreev 1999, Williams et al 2001) confirmed the radio-adaptation of the local species of Chironomid midge. Various population genetics and cytogenetic analysis revealed that specific chromosomal inversions were stabilised in the irradiated natural population of C. belatonicus from the Chernobyl region (Michailova and Petrova 1994).…”
Section: Introductionmentioning
confidence: 90%
“…In Drosophila much work has been carried out on the response of different strains to radiation (Parsons et al 1969) and one study showed that a strain originating from a region of high natural radiation was significantly more radiation resistant to the induction of dominant lethal mutations than a strain from a region with a much lower background radiation (Cordeiro et al 1973). Adaptation of a natural population of Chironomids to chronic low-level radiation has also been reported (Blaylock 1965(Blaylock , 1966, as well as cytogenetic changes and morphological deformities of Chironomid populations subsequent to the Chernobyl nuclear disaster (Michailova and Petrova 1994;Williams et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…1973). Adaptation of a natural population of Chironomids to chronic low‐level radiation has also been reported (Blaylock 1965, 1966), as well as cytogenetic changes and morphological deformities of Chironomid populations subsequent to the Chernobyl nuclear disaster (Michailova and Petrova 1994; Williams et al. 2001).…”
Section: Discussionmentioning
confidence: 98%
“…In attempts to clarify the effects of radiation on mammals, birds, and arthropods, phenotypic abnormalities have been evaluated based on adults (Møller 1993(Møller , 2002Møller and Mousseau 2006;Yablokov et al 2009) except in a few studies (Williams et al 2001). However, the effects of radiation emerge most strongly in hatchlings or newborns, resulting in mortality and phenotypic abnormalities, as shown in irradiation experiments (Elbadry 1965;Tilton et al 1966;McGregor and Newcombe 1968;Vereecke and Pelerents 1969;Matranga et al 2010) as well as field studies in Chernobyl (Krivolutzkii and Pokarzhevskii 1992;Krivolutsky 1995).…”
Section: Introductionmentioning
confidence: 99%